Qirāʾah Tafsīriyyah li-Āyāt al-Jilbāb: Dirāsah Muqāranah bayna Aminah Wadud wa-Muhammad Quraish Shihab - Ahmad Rifai Rohman (Al-Zahra : Journal for Islamic and Arabic Studies, 2025)
This study examines the Qur’anic interpretation of the verses on jilbab through a comparative analysis of Amina Wadud and M. Quraish Shihab, employing a qualitative and comparative approach. Moving beyond previous studies that primarily focus on methodological differences between modern and traditional tafsir, this research explores how these differences shape distinct understandings of the function of jilbab and the authority of the Qur’anic text. The findings reveal three main points. First, both scholars share a substantive common ground in considering the socio-historical context and ethical objectives of the jilbab verses rather than adhering to a purely literal reading. Second, their principal divergence lies in the conceptualization of jilbab: Amina Wadud views it primarily as a form of social-ethical guidance that is not necessarily legally binding, whereas M. Quraish Shihab understands it as a normative sharīʿah ruling with legal implications, while still allowing contextual considerations in its application. Third, this divergence reflects differing conceptions of textual authority, with Amina Wadud emphasizing the Qur’an’s universal values, and M. Quraish Shihab grounding authority in the normative structure of the text and established exegetical principles. The study concludes that differences in interpreting the jilbab verses are not merely methodological, but also epistemological.